In vivo evaluation of the therapeutic effect of Streptococcus thermophilus isolated from camel milk on intestinal disorders - LAICHE, Ammar Touhami; BENINE, Chaima (Studia Universitatis Babeș-Bolyai Biologia, 2024)
This study aimed to isolate, select, and evaluate lactic acid bacteria possessing probiotic properties. Isolates obtained from camel milk from El-Oued region in Algeria were investigated for their potential effect on intestinal disorders in Wistar rats. The results relating to the selection of probiotic strains confirm that one strain, identified as Streptococcus thermophilus exhibited the best probiotic activity, with an important tolerance to different degrees of pH and to bile salts, and a remarkable antibacterial activity and resistance to antibiotics. During in vivo studies, the administration of isolated lactic acid bacteria was evaluated after inducing intestinal disorders in rats. The microscopic observations of the histological section of the intestine showed an almost complete disappearance of the damages in the intestinal structure. The haematological parameters were in agreement with the results of the histological sections. Article history: Received 27 April 2024; Revised 12 September 2024; Accepted 13 October 2024; Available online 10 December 2024